The French Foreign Legion: a complete history of the lengendary fighting force (HarperCollins Publishers, 1991)
No other military force in the last century and a half has captured the popular imagination to such a degree or has been so surrounded by romance, legend, and mystery as the French Foreign Legion. This book is the most complete and balanced history of the Legion ever written.